Infâncias urbanas e experiências de cidadania a partir do espaço público - Barros, Robertha Georgya Galdino de (2023)
The theme of childhood has been studied by researchers from the most diverse areas of knowledge all over the world. In an attempt to situate it under perspectives that advance over the traditional view of a theme conceptually linked to the family and the school, this research opens to new narratives and looks, placing the city and the public space as important elements that connect to the theme as powerful means of learning and formation of citizenship of the contemporary child. The research is theoretical-descriptive and makes use of Merleau-Ponty's phenomenology (1999) as one of the ways to analyse the relationship between the experiences of appropriation of the public space by the child and the formation of children's citizenship. The general aim of the research is, therefore, to analyse the educational function of space in the formation of children's citizenship. As specific objectives, we sought to: explore a theoretical framework of key categories on the theme; discuss the experiences of production of space and formation of child citizenship in the Extension Project Meu Pé na CalçadaLarange-Lima: Intimations between child and neighbourhood and, finally, analyse two experiences between the nuances of the body/play during social confinement at the beginning of the SARS-CoV-2 pandemic. As a starting point, we understand that childhood is plural, hybrid, which is justified by the different social and cultural contexts that contribute to the numerous possibilities of being a child (JENKS, 1982) and that it constitutes one of the social groups most sensitively affected by factors such as poverty and social exclusion in the globalizing context of the neo-liberal society, which reproduces a paradigm of invisibility (TOMÁS; SOARES, 2004). Both the understanding of the child from the perspective of Dasein (HEIDEGGER, 2008), which places the relational and symbolic aspect of space in line with the idea of affection and care for the other, and the studies and reflections anchored in an interdisciplinary theoretical and methodological basis proper to Environmental Sciences, lead to ratify the pedagogical dimension of the city and the educational function of public space. This perspective opens to the understanding that the space is a powerful means of forming children's citizenship, as a collective process and possible as a daily social practice of the child with the city, which must go beyond the spectrum of the child's social participation in the construction of the city. It must reach, however, the understanding that the experiences between body/play also in domestic environments, for instance, produce new forms of knowledge and learning.